How to use and how not to use certified reference materials in industrial chemical metrology laboratories. Issue 2 (June 2020) - Sieber, John R.
Abstract : As a producer of certified reference materials (CRMs), NIST faces high demand for Standard Reference Materials (SRMs). The demand is exacerbated by widespread misuse of CRMs. When should one use CRMs? When should one not use CRMs? Must labs always use NIST SRMs? How can labs demonstrate analytical capabilities for their accreditation scopes? Why so many questions? Standards developers, laboratory accreditors, and laboratory staff must be able to understand these topics with respect to quality systems in compliance with ISO/IEC 17025. They must calibrate and validate test methods and document traceability to the International System of Units (SI). Many people working in laboratory accreditation and under the umbrella of a quality system do not fully understand what these things are, let alone the language of chemical metrology. On average, they have little training in analytical chemistry, elemental analysis, and reference material development. It is hoped this paper will impress upon the reader the need for understanding how CRMs can be best used in the laboratory. This paper provides a brief background on the above problems and then looks at some of the support and reference information provided by NIST to metals and mining industries labs, commercial CRM producers, and accrediting bodies. The concepts and guidance apply broadly to chemical metrology and fundamental analytical chemistry. The paper includes examples (some from X-ray fluorescence spectrometry) to illustrate concepts.